Implications Of Illegal Community Mining For Economic Development In Bangka Regency, Indonesia - Rahayu, Derita Prapti; Rahayu, Sri; Faisal, Faisal; Wulandari, Cahya; Hassan, Muhamad Sayuti (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2023)
The Kepulauan Bangka Belitung Province, Indonesia, is renowned for its extensive history of tin mining, a pivotal component of the local economy. Notably, this mining encompasses operations conducted by both corporate entities and individual community members, shaping the region's socio-economic landscape. This research seeks to investigate the multifaceted implications of community-led tin mining activities in Bangka Belitung. Employing a qualitative and socio-legal approach, the study underscores its significance in the acquisition of high-quality data derived from site visits, comprehensive surveys, and interviews with the diverse local community, encompassing various subsistence groups and socio-economic backgrounds. Our findings indicate that individual community mining activities have indeed contributed positively to the economic growth of the Kepulauan Bangka Belitung Province, particularly in the Bangka Regency. However, they also manifest negative repercussions in terms of illegal mining, which adversely affects state revenue due to unregistered taxpayers. Furthermore, these activities hinder human resource development and highlight a deficiency in the supervision of reclamation efforts undertaken by artisanal mining operators. Therefore, the study emphasizes the imperative for government intervention, focusing on community mining permits to enforce reclamation regulations and ensure sustainable, responsible mining practices.